Vietnamese culture in chopstick use compared to western culture in utensil use = Wietnamska kultura korzystania z pałeczek a kultura posługiwania się sztućcami w krajach zachodu - Nguyen, Thuy Thi Thu (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Culinary culture is an interesting and meaningful aspect that has captivated the scholars` attention recently. This article introduces and analyses some features in chopstick use of Vietnamese culture in comparison with the use of utensils (forks, knives, spoons) in Western culture. Comparative cultural studies viewpoint and typological method were applied to highlight the di?erences and similarities in tangible and intangible culture of those cultures. The ?ndings of the research will help the audience have better understanding and knowledge of cultures in the world aiming to orientate towards the empathy and mutual appreciation.
Keywords: chopstick use; chopsticks; utensil; Vietnamese culture; Western culture; comparative cultural studies; eating devices; użycie pałeczek; pałeczki; kultura wietnamska; kultura zachodnia; kulturoznawstwo porównawcze; przybory do jedzenia